Analisis Implementasi Hukum Waris Islam dalam Kehidupan Masyarakat Urban - Hasbi Umar; Husin Bafadhal; Della Anggi Pratiwi; Rama Satria Putra; Arip Hidayatullah (Lembaga Yasin AlSys, 2026)
Although the implementation of Islamic inheritance law has been widely studied, research that specifically highlights its practice in the context of urban communities influenced by modernization, legal pluralism, and socioeconomic factors remains relatively limited. This study aimed to examine the practice of implementing Islamic inheritance law and identify various challenges faced by urban communities in implementing it. This study used a qualitative approach with a case study design, involving 15 informants selected using purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using thematic analysis techniques. The results showed that the implementation of Islamic inheritance law in urban communities had not been carried out optimally. This condition was influenced by limited public understanding, the dominant influence of customary law and positive law, as well as economic considerations and family harmony. In addition, there was a tendency for inheritance distribution to be carried out through deliberation, which was not always in accordance with the provisions of faraidh. This finding contributes to the development of Islamic law studies, particularly regarding the adaptation of law to social change, and expands understanding of the dynamics of inheritance law implementation in modern society. Thus, improving Islamic inheritance law literacy among urban communities and the active involvement of religious leaders and relevant institutions are needed to provide comprehensive education and optimize the implementation of Islamic inheritance law more proportionally.